Temporal representation in narratives of forced removals : a narrative analysis of life story texts - Bennett, Bonita (Centre for Applied Language and Literacy Studies and Services in Africa, 2014)
In this thesis I have examined the life stories of three victims of forced removals. It is based on an understanding that there is much that we can learn from the lives of 'ordinary people' and that the oral medium is a rich source of understanding other aspects of society. Chapter 1 sketches the background of this study, and the socio-political context within which it has grown. In the main theory section (chapter 2), I provide a general overview of the tools of narrative-based discourse analysis which I have used for my work and lead into a consideration of theories of memory and time. I focus particularly on aspects of representation of time in narrative and explore the nature of traumatic memory in relation to this. In chapter four, my analysis draws attention to the different ways in which narrators make sense of the traumatic event in their lives. In fact, my analysis demonstrates that trauma shares fewer features with 'events' (as understood by Portelli, Ricouer and others), and seems to correspond more closely to an understanding of it as 'duration'. I conclude that the concept of linear time is not the organising principle in the narratives which I have examined, and that the forced removal has been a central occurrence around which the rest of life - and narrating about life is understood.